Identificação de microrganismos resistentes ao herbicida ácido 2,4-diclorofenóxiacético (2,4-D) em solos de Rondônia, Brasil - Higino Mussy, Marília; Brucha, Gunther; Gomes Reis, Mariza; Ikeda Ushimaru, Priscila [UNESP]; Yamashita, Miyuki; Rodrigues Bastos, Wanderley (My University, 2013)
Pesticide application has become very important in controlling pests and other infestations that attack crops and pastures. The study of these organic compounds in the environment and especially the changes they undergo during their incubation periods in soils are still largely unknown, as are their equivalent effects on living organisms. The herbicide 2,4-dichlorophenoxyacetic acid (2,4-D) is widely used to control broadleaf weeds that infest pastures and plantations in the Amazon region. This herbicide is classified toxicologically as Class I; that is, highly toxic. The aim of this study was to isolate and identify microorganisms from soils of the Amazon region, resistant to the toxicity of 2,4-D. For this, aliquots of soil samples were incubated in a mineral medium containing 200mg·l-1 of the compound as sole carbon source. After 18 transfers, the organisms growing in the medium were isolated and identified phylogenetically. The results of the 16S DNA sequencing fragment amplified from strains isolated suggest that Methylobacterium sp., Xanthobacter autotrophicus, Burkholderia cenocepacia, Aurantimonas sp., Campylobacter jejuni and Methylobacterium chloromethanicum, all described in the literature as potential degraders of organic compounds, were present in the soils of the state of Rondônia. These samples were resistant to microbial toxicity of 2,4-D.
Identification of microorganisms resistant to the herbicide 2,4-dichlorophenoxyacetic acid (2,4-d) in soils of Rondonia, Brazil